2021
DOI: 10.5304/jafscd.2021.102.035
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on local government stakeholders' perspectives on local food production

Abstract: Local food production (LFP) can play an impor­tant role in ensuring access to food during supply chain disruptions. Because the drafting, adoption, and implementation of policies regulating LFP is under the purview of local governments in many U.S. states, researchers at University of Florida, Institute of Food and Agricultural Sciences Exten­sion conducted a study to assess whether COVID-19 affected local government stakeholders’ (LGS) (N=92) perspectives on LFP and the role that LFP can play in responding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
1
17
0
3
Order By: Relevance
“…Despite the cultural rootedness of the principles of intra-community solidarity, reciprocity, and collective support (e.g., [76] ), Schwarz et al [78] found that monetization of inter-household exchanges, alongside the relatively new values associated with modernity and democracy, “gradually erode the collective nature of the traditional social system.” Dacks et al [27] similarly found that higher market integration resulted in weaker sharing networks. A recent investigation with small-scale fishing communities in Indonesia suggests that market integration also directly increases fishers’ vulnerability to the shocks associated with COVID-19 [101] . Steenbergen et al [81] noted that the increased transition to cash-based economies in villages in Vanuatu exacerbated vulnerability to the shocks associated with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the cultural rootedness of the principles of intra-community solidarity, reciprocity, and collective support (e.g., [76] ), Schwarz et al [78] found that monetization of inter-household exchanges, alongside the relatively new values associated with modernity and democracy, “gradually erode the collective nature of the traditional social system.” Dacks et al [27] similarly found that higher market integration resulted in weaker sharing networks. A recent investigation with small-scale fishing communities in Indonesia suggests that market integration also directly increases fishers’ vulnerability to the shocks associated with COVID-19 [101] . Steenbergen et al [81] noted that the increased transition to cash-based economies in villages in Vanuatu exacerbated vulnerability to the shocks associated with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has created a global health and economic crisis that has highlighted the fragility of globalized food systems to external shocks ( [13] , [56] , [62] , [101] ). In the context of fisheries, border closures and social distancing measures led to the closure of ports and the vast reduction of shipping and air freight [69] , as well as reduced access to urban markets [13] .…”
Section: Introductionmentioning
confidence: 99%
“…These knowledge gaps have been exposed by "previously unimaginable disruptions in the food supply chain" (Nayga & Zilberman, 2020, p. 34). Campbell (2021) discussed how COVID-19 affected local government perceptions of local food systems and their role in public health emergencies-a worthy endeavor but a missed opportunity to acknowledge and investigate regional food systems.…”
Section: Introductionmentioning
confidence: 99%
“…Businesses also contributed to each other's survival, as interviewees reported that the continued operation of their foodservice businesses had effects up and down the supply chain, supporting farmers and meeting the evolving needs of consumers. These collaborative and community-based support networks, both state-sponsored and independent, might be useful models for other states, as referenced by Campbell (2021) and Ammons et al (2021). Some businesses appointed heads of health and safety to monitor information sources and create and manage operating procedures based on evolving health guidance.…”
Section: Introductionmentioning
confidence: 99%